THE EFFECT OF WORK COMMITMENT AND JOB SATISFACTION ON EMPLOYEE WORK SPIRIT AT THE REGIONAL SECRETARIAT OF CENTRAL TAPANULI DISTRICT - Hafiz Aulia Rahman; Mansur Tanjung; Yenni Sofiana Tambunan (Journal Boas : Business, Economics, Accounting And Management, 2025)
This study aims to determine the effect of work commitment and job satisfaction on employee morale at the Regional Secretariat of Central Tapanuli Regency. This study used a quantitative approach with a descriptive approach. The sample size consisted of 91 respondents. The results showed a regression equation of Y = 98.226 + 0.242x1 + 0.502x2, indicating that work commitment and job satisfaction influence work morale. A t-test revealed a calculated t-value of 2.366 for work commitment, greater than the t-table of 1.987. This indicates that work commitment influences work morale. Furthermore, a t-test revealed a calculated t-value of 5.862 for work satisfaction, greater than the t-table of 1.987. This indicates that job satisfaction influences work morale at the Regional Secretariat of Central Tapanuli Regency. The calculated F value of 43.339 is greater than the F table value of 3.10. This indicates that work commitment and job satisfaction influence work morale in the Central Tapanuli Regency Regional Secretariat. This means that Ha is accepted and Ho is rejected.